2010
DOI: 10.1302/0301-620x.92b12.22141
|View full text |Cite
|
Sign up to set email alerts
|

What happens to femoral neck bone mineral density after hip resurfacing surgery?

Abstract: The major advantage of hip resurfacing is the decreased amount of bone resection compared with a standard total hip replacement. Fracture of the femoral neck is the most common early complication and poor bone quality is a major risk factor. We undertook a prospective consecutive case control study examining the effect of bone mineral density changes in patients undergoing hip resurfacing surgery. A total of 423 patients were recruited with a mean age of 54 years (24 to 87). Recruitment for this study was depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…In both studies a comparison was made with a group of younger patients who had also been treated with resurfacing but without comparison to the current standard of care. Older women are usually regarded 10,9,8,7 for pain, walking, function, and activity, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both studies a comparison was made with a group of younger patients who had also been treated with resurfacing but without comparison to the current standard of care. Older women are usually regarded 10,9,8,7 for pain, walking, function, and activity, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The conservative nature and stability of hip resurfacing arthroplasty (HRA) make it a viable alternative to conventional total hip arthroplasty (THA) in young and active patients (1,2) because of the preservation of bone mineral density over time in the proximal femur (3)(4)(5)(6)(7) and because of the prospect of potentially easy and successful revision surgery should this be necessary (8)(9)(10)(11). Conventional THA is extremely successful in older patients with hip arthritis and remains the treatment 'gold standard' for this group of patients (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…However, a femoral neck fracture is the most common complication, which makes poor bone quality a major risk factor. 10 In fact, the femoral neck loses bone mineral density (BMD) in the perioperative phase (fi rst 3 months) of healing, which poses a major risk for individuals who already have poor bone quality. 11 , 12 In 2012, Matharu et al reported the prevalence of femoral neck fractures after HRA in a group of 3076 individuals.…”
Section: Bone Quality and Morphologymentioning
confidence: 99%
“…21,101 As for the femur, existent anatomy and preoperative BMD probably affect the extent of the phenomenon. 104,105 Spontaneous narrowing of the femoral neck (>10% of femoral neck diameter) is a phenomenon of unknown origin that may be seen in 27.6% cases at 5 years 106 (Figure 5a). This usually occurs as a spontaneous acute event (not necessarily traumatic) and is thought to result from postsurgical avascular necrosis (AVN) of the femoral head and/or neck.…”
Section: Radiographic Changes With Timementioning
confidence: 99%